HXE 317 - Literature And Film June 2016 - PPIK, Pusat Pengajian Ilmu Kemanusiaan (Universiti Sains Malaysia, 2016)
Please check that this examination paper consists of TWO pages of printed material before you begin the examination. Answer THREE questions.